Assessment of the success rate of endodontically treated patients attending outpatient polyclinic - Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Abdul Majeed, Kais Raad; Abdul Qader, Omar Abdul Jabbar (Wolter Kluwer - Medknow, 2018)
Objectives: The aim of this study is to determine the success rate of the endodontically treated teeth in patients attending the Polyclinic, Kulliyyah of Dentistry, International Islamic University Malaysia (IIUM), from 2012 to 2015. Materials and Methods: A retrospective study involved endodontically treated teeth of patients attending the Polyclinic, Kulliyyah of Dentistry, IIUM, from 2012 to 2015. Clinical and radiographic data were recorded and classified as successful or failed, and further analyzed by Fisher’s exact test to measure the correlation between the variables using SPSS software version 16.0. Kappa test was used to measure the overall relationship between clinical and radiographic findings. Results: A total of sixty teeth were evaluated clinically and radiographically, the overall success rate was 85% (n = 51). Correlation between the variables showed nonsignificant (P > 0.05) in the success rate among age, gender, and race, upper and lower arches and between anterior and posterior teeth at the time of treatment. At postendodontic fixed restorations, the variables showed statistically significant relationship with the success rate (P < 0.05). Conclusions: Patients with no signs and symptoms and with no radiographical changes at the the time of clinical examination ,showed the highest percentage of success rate (85%) of postendodontic fixed restorations. Age, gender, and race have no significant relations with the success rate of endodontically treated teeth.